Deutschland - Beginn des modernen Photojournalismus - Gidal, Tim N. (Luzern : Bucher, 1972)
Bosshard, Walter ; Salomon, Erich ; Munkacsi, Martin ; Ruge, Willi ; Eisenstaedt, Alfred ; Gidal, Tim N. ; Kertész, André ; Umbo ; Lechenperg, Harald ; AIZ.
Schenking Eric de Kuyper
boek